2022
DOI: 10.3390/ma15238616
|View full text |Cite
|
Sign up to set email alerts
|

Selecting the Best Performing Modified Asphalt Based on Rheological Properties and Microscopic Analysis of RPP/SBS Modified Asphalt

Abstract: As an asphalt modifier, waste polypropylene (RPP) can not only optimize the performance of asphalt but also greatly alleviate the problem of waste plastic treatment, effectively reducing environmental pollution and resource waste. In order to evaluate the influence of RPP and styrene butadiene styrene (SBS) on asphalt performance, the application of RPP in modified asphalt pavement has been expanded. In this study, a dynamic shear rheometer (DSR), bending beam rheometer (BBR) and other instruments were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…They replaced materials to improve the shock absorption effect of roads, utilizing inherently elastic rubber materials to enhance elasticity and shock absorption. The shock absorption effect was evaluated using a drop ball impact vibration test [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…They replaced materials to improve the shock absorption effect of roads, utilizing inherently elastic rubber materials to enhance elasticity and shock absorption. The shock absorption effect was evaluated using a drop ball impact vibration test [21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Filip et al [11] subjected waste polystyrene pellets to a cracking reaction at 400 • C with a catalyst of volcanic ash; their results showed that the conversion of polystyrene pellets was significantly higher and the product liquid hydrocarbons could be converted into qualified aviation fuel. Lei et al [12] set different reaction temperatures for the high-temperature cracking conversion of waste plastics catalyzed by activated carbon; the optimal product result was a high-quality blend of 85% aviation fuel and 15% diesel fuel. Sharma et al [13] performed the pyrolysis of high-density polyethylene plastics, during which silicates were added to catalyze the reaction; they obtained a high-utilization mixture of hydrocarbon products with similar boiling points to petroleum, with two-thirds of the liquid products and one-third of the gaseous solid products.…”
Section: Introductionmentioning
confidence: 99%